Popeye [videorecording (Blu-Ray)] - Williams, Robin, 1951-2014; Duvall, Shelley, 1949-2024; Walston, Ray, 1917-2001; Hurt, Wesley Ivan; Nillson, Harry; Nillson, Harry; Feiffer, Jules (Paramount, 2020)
The legendary, beloved anvil-armed sailor of the seven seas comes magically to life in a delightful musical. Popeye's devoted long-limbed sweetie, Olive Oyl, one of many loveable characters join the ₁sailor man₂ in his adventures in the harbor town of Sweethaven.